2017
DOI: 10.1016/j.tourman.2016.12.009
|View full text |Cite
|
Sign up to set email alerts
|

Food tourism policy: Deconstructing boundaries of taste and class

Abstract: Recent discussions from the journal of tourism management call for more critical deconstructions of the political and economic structures that shape policy and planning. The present paper takes up this call, using a post-structualist framework to examine Scotland's food tourism landscape. Utilising Foucauldian discourse analysis to deconstruct 2,312 media sources collected through a Factiva database search, we illustrate how policy discourses privilege middle class cultural symbols through official food touris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

2
8

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 42 publications
(49 reference statements)
0
31
0
3
Order By: Relevance
“…Adventure tourism today includes more than just high-adrenaline activities. Commercially, manifestations of slow(er) adventure are increasingly applied (Slow Adventure in Northern Territories 2016; The Slow Adventure 2016; Slow Adventure Company 2016), offering activities as simple as star gazing, open water swimming, wild camping or cooking foraged foods (see Varley and Semple 2015;de Jong and Varley 2017), which trigger the immediate mental and bodily sensations of the taste of the food, of being connected to nature, of being comfortable with place there, with one's self and the others. 'Slowness' in these contexts, must therefore follow two crucial principles: firstly, taking time to dwell in nature, and secondly, performing a lived attachment to a particular place, augmented via the presence of a skilled guide.…”
Section: Discussionmentioning
confidence: 99%
“…Adventure tourism today includes more than just high-adrenaline activities. Commercially, manifestations of slow(er) adventure are increasingly applied (Slow Adventure in Northern Territories 2016; The Slow Adventure 2016; Slow Adventure Company 2016), offering activities as simple as star gazing, open water swimming, wild camping or cooking foraged foods (see Varley and Semple 2015;de Jong and Varley 2017), which trigger the immediate mental and bodily sensations of the taste of the food, of being connected to nature, of being comfortable with place there, with one's self and the others. 'Slowness' in these contexts, must therefore follow two crucial principles: firstly, taking time to dwell in nature, and secondly, performing a lived attachment to a particular place, augmented via the presence of a skilled guide.…”
Section: Discussionmentioning
confidence: 99%
“…Çünkü günümüzde pek çok birey kendi yaşadıkları çevreden daha farklı yenilen, giyinilen, davranılan yerleri deneyimlemek için turizm hareketine katılmaktadır (Reisinger, 2009). Böylece turistler deneyimleri esnasında kendi kültürlerini aşar ve farklı kültürleri deneyimleme olanağı bulurlar (Jong ve Varley, 2017). Bu sayede yemek tüketimi turizmin önemli bir tamamlayıcısı olmaktan çıkıp, turizmi oluşturan önemli boyutlardan biri haline gelmiştir (Quan ve Wang, 2004).…”
Section: Yerel Yiyecek Tüketim Motivasyonlarıunclassified
“…Gastronomic Tourism allows them to escape from their usual environment and enter into a world of novelty. It can be concluded that more and more tourists are looking for concrete learning experiences, in which gastronomy plays a predominant and central role (Jong & Varley, 2016). Individuals seeking this type of Tourism aren't necessarily the same individuals engaged in other non-gastronomic activities (UNWTO, 2012).…”
Section: Concept and Profile Of Gastronomic Touristmentioning
confidence: 99%